The prognostic value of diagnostic tools in patients with seropositive myasthenia gravis: a retrospective study of 31 cases - Gryb, V.A.; Tretyakova , A.I.; Titov , I.I.; Chudovska, L.D.; Nasonova, T.I.; Slobodin, T.M.; Doroshenko, O.O. (Medicni Perspektivi, 2021)
To confirm the diagnosis of myasthenia gravis (MG), in addition to clinical observation of the muscle weakness dynamics, pharmacological and functional tests, Computed tomography/Magnetic resonance imaging (CT/MRI) of the mediastinum, detection of antibodies to acetylcholine receptors (AChR) and to muscle specific tyrosine kinase (MuSK)/; electrophysiological tests are used: rhythmic nerve stimulation (RNS)/decrement test and electromyography of a single muscle fiber (single-fiber EMG (SF-EMG)/jitter). The aim of our study is to determine the possible relationship between the level of antibodies to AChR and the decrement test value, to verify a correlation between SF-EMG and the severity of MG seropositive to AChR. To evaluate the effectiveness of pathogenetic treatment and prediction of the duration of remission according to the results of the study. A total of 31 patients with myasthenia gravis seropositive to AChR were examined, among whom there were 19 (61.3%) women aged 19 to 74 years. The pattern of muscle weakness was evaluated by a score of the International Clinical Classification of Severity of Myasthenia gravis scale (MGFA). The presence of respiratory failure and its degree was assessed by spirography. The number of antibodies to AChR was determined using enzyme-linked immunosorbent assay (ELISA). The criteria for inclusion in the study were the confirmed diagnosis of seropositive myasthenia gravis with an AChR antibody level of more than 0.5 nmol/L. All patients underwent electrophysiological studies. Patients were examined three times: 1) at the time of visiting the doctor (in the hospital or on an outpatient basis); 2) in 16 and 3) in 24 weeks from the start of the study. Depending on the clinical condition of the patients the following treatment was prescribed: pyridostigmine, methylprednisolone, azathioprine. Statistical analyses were performed using the statistical computing environment R (R Core Team). In the dynamics of observation, a decrease in the level of antibodies to AChR and an improvement in the condition of patients according to the MGFA classification were generally observed but no correlation was found between the severity of MG and the level of antibodies to AChR during the first visit (Kruskal-Wallis test: H (4, N=31)=2.23 p=0.69); during the second visit (Kruskal-Wallis test: H (5, N=31)=9.44 p=0.09), as well as during the third visit (Kruskal-Wallis test: H (2, N=30)=2.74 p=0.25). A correlation was found between the concentration of antibodies to AChR and a thymectomy in the clinical history (Kruskal-Wallistest: H (1, N=7)=3.153752 p=0.07): over time, the level of antibodies decreased. Decrement test deviations were detected in 23 (74.2%) of the 31 patients, SF-EMG – in 20 (95%) of 21 patients. Abnormal jitter was recorded in 100% of cases with a generalized form of myasthenia gravis. During all three visits, a correlation was determined between the highest decrement test of symptomatic muscle and MG severity according to MGFA (r=0.39; p=0.042), (r=0.35; p=0.048), (r=0.41; p=0.039); and also between the jitter value and MG severity (r=0.54; p=0.032) (r=0.35; p=0.048), (r=0.61; p=0.034 respectively). Analysis of the contingency tables using the exact Fisher test provided information on the best method of treating patients. We consider that the most effective prognostic test that may affect the choice of further treatment is SF-EMG. However, due to the difficulties of using this method in routine practice, rhythmic nerve stimulation (RNS) test in clinically weak muscles should be recommended. It is not recommended to monitor antibodies to AChR in order to predict the course of the disease, it is better to use this test only for the diagnosis of seropositive myasthenia gravis.